Beneficial effects of adenotonsillectomy in children with sickle cell disease. Issue 4 (26th October 2020) - Liguoro, Ilaria; Arigliani, Michele; Singh, Bethany; Van Geyzel, Lisa; Chakravorty, Subarna; Bossley, Cara; Pelidis, Maria; Rees, David; Inusa, Baba P.D.; Gupta, Atul
Tonsillectomy and adenoidectomy (T&A) is frequently performed in children with sickle cell disease (SCD). Our aim was to evaluate the impact of this surgery on overnight oxygenation and rates of complications in these patients. Children with SCD who underwent T&A between 2008 and 2014 in two tertiary hospitals were retrospectively evaluated. Overnight oximetry and admission rates due to vaso-occlusive pain episodes (VOEs) and acute chest syndrome (ACS) in the year preceding and following the surgery were compared. 19 patients (10 males, 53%) with a median age of 6 years (range 3.5–8) were included. A significant increase of mean overnight arterial oxygen saturation measured by pulse oximetry ( S pO2 ) (from 93±3.6% to 95.3±2.8%, p=0.001), nadir S pO2 (from 83.0±7.1% to 88±4.1%, p=0.004) and a reduction of 3% oxygen desaturation index (from a median value of 5.7 to 1.8, p=0.003) were shown. The mean annual rate of ACS decreased from 0.6±1.22 to 0.1±0.2 events per patient-year (p=0.003), while the mean cumulative rate of hospitalisations for all causes and the incidence of VOEs were not affected. T&A improved nocturnal oxygenation and was also associated with a reduction in the incidence of ACS at 1-year follow-up after surgery. In children with SCD, this retrospective analysis suggests that tonsillectomy and adenoidectomy may have a beneficial effect on nocturnal oxygenation level and the rate of ACS. This finding will need further confirmation in prospective and larger studies. https://bit.ly/3gL6gaU